Modeling and solution of methane jet diffusion flames - Lorenzzetti, Greice da Silva; Bortoli, Álvaro Luiz de; Marczak, Lígia Damasceno Ferreira (VETOR - Revista de Ciências Exatas e Engenharias, 2010)
The aim of this work is to model a jet diffusion flame, to show the corresponding proof of existence of solutions, and to present the numerical results. The model is based on the flamelet equations for the chemistry and on the mixture fraction for the flow. Numerical tests are carried out for Sandia Flame D and the results are found to compare well with available data in the literature.